Combined citicoline and docosahexaenoic acid treatment improves cognitive dysfunction following transient brain ischemia - Eri Nakazaki; Yasushi Yabuki; Hisanao Izumi; Yasuharu Shinoda; Fumiko Watanabe; Yukihiro Hishida; Ayako Kamimura; Kohji Fukunaga (Elsevier, 2019)
Phospholipids are structural components of cellular membranes that play important roles as precursors for various signaling pathways in modulating neuronal membrane function and maintenance of the intracellular environment. Phosphatidylcholine (PtdCho) is the most abundant cellular phospholipid. Citicoline and docosahexaenoic acid (DHA) are essential intermediates in the synthesis of PtdCho. Both PtdCho intermediates have independently shown neuroprotective effects in cerebral ischemia, but their combined effect is unknown. This study aimed to investigate the combined effect of oral citicoline and DHA treatment on improvement of cognitive deficits following cerebral ischemia using a 20-min bilateral common carotid artery occlusion (BCCAO) mouse model. BCCAO ischemic mice were treated for a total of 11 days with a combination of citicoline (40 mg/kg body weight/day) and DHA (300 mg/kg body weight/day) or each alone. Combined citicoline and DHA synergistically and significantly improved learning and memory ability of ischemic mice compared with either alone. Further, citicoline and DHA treatment significantly prevented neuronal cell death, and slightly increased DHA-containing PtdCho in the hippocampus, albeit not significantly. Taken together, these findings suggest that combined citicoline and DHA treatment may have synergistic benefits for partially improving memory deficits following transient brain ischemia. Keywords: Citicoline, DHA, Bilateral common carotid artery occlusion, Neuroprotection, Memory